Immunogenicity in animals of a polysaccharide-protein conjugate vaccine against type III group B Streptococcus - Wessels, M R; Paoletti, L C; Kasper, D L; DiFabio, J L; Michon, F; Holme, K; Jennings, H J (The Journal of clinical investigation, 1990)
The native capsular polysaccharide of type III group B Streptococcus elicits a specific antibody response in only 60% of nonimmune human subjects. To enhance the immunogenicity of this polysaccharide, we coupled the type III polysaccharide to tetanus toxoid. Prior to coupling, aldehyde groups were introduced on the polysaccharide by controlled periodate oxidation, resulting in the conversion of 25% of the sialic acid residues of the polysaccharide to residues of the 8-carbon analogue of sialic acid, 5-acetamido-3,5-dideoxy-D-galactosyloctulosonic acid. Tetanus toxoid was conjugated to the polysaccharide by reductive amination, via the free aldehyde groups present on the partially oxidized sialic acid residues. Rabbits vaccinated with the conjugate vaccine produced IgG antibodies that reacted with the native type III group B streptococcal polysaccharide (3/3 rabbits), while rabbits immunized with the unconjugated type III polysaccharide failed to respond (0/3 rabbits). Sera from animals receiving conjugate vaccine opsonized type III group B streptococci for phagocytic killing by human peripheral blood leukocytes, and protected mice against lethal challenge with live type III group B streptococci. The results suggest that this method of conjugation to a carrier protein may be a useful strategy to improve the immunogenicity of the type III group B Streptococcus polysaccharide in human subjects.